Advancing conceptual clarity in marketing science: Delineating process and systems perspectives on value co-creation - Makkonen, Hannu; Aspara, Jaakko; Grönroos, Christian; Mäntymäki, Matti (Sage publications, 2026)
Conceptual clarity is fundamental to accumulating knowledge in marketing science. This study investigates the construct of value co-creation to assess its conceptual clarity in the academic literature and inform broader theory development in marketing. Drawing on a systematic literature review and statistical analysis of 1224 peer-reviewed articles, we find that while conceptual clarity has improved over time, it remains fragmented. Surprisingly, marketing- and service-focused journals do not exhibit higher conceptual clarity than adjacent fields; moreover, journal ranking correlates negatively with conceptual clarity, whereas author affiliation with prestigious institutions correlates positively with conceptual clarity. To advance the field, we propose a conceptual framework that distinguishes between process and systems perspectives of value co-creation and outline future research avenues grounded in this distinction. We contribute to marketing theory by delineating the value co-creation concept and offering actionable tools for enhancing conceptual clarity, thus supporting more coherent further theorizing and empirically robust research.
Keywords: value co-creation; co-production; service-dominant logic; systematic literature review; conceptual clarity; service process; fi=Markkinointi|en=Marketing|